2017
DOI: 10.1002/2017jb014147
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐dependent permeability and wave dispersion in tight cracked rocks: Experimental validation of simple effective medium models

Abstract: We experimentally assess the impact of microstructure, pore fluid, and frequency on wave velocity, wave dispersion, and permeability in thermally cracked Carrara marble under effective pressure up to 50 MPa. The cracked rock is isotropic, and we observe that (1) P and S wave velocities at 500 kHz and the low‐strain (<10−5) mechanical moduli at 0.01 Hz are pressure‐dependent, (2) permeability decreases asymptotically toward a small value with increasing pressure, (3) wave dispersion between 0.01 Hz and 500 MHz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 49 publications
4
36
2
Order By: Relevance
“…Without differential stress, hydrostatic stress may be enough to close cracks, and hence, they are not observable from elastic properties. However, while a strong recovery is observed on wave velocity during subsequent unloading, damage produced during loading remains within the rock specimens and are expected to affect other physical properties, such as permeability or porosity (Sarout et al, ). Our results suggest that elastic measurement of natural rock samples should be made with both confining pressure and deviatoric stress to highlight the full amount of damage recorded from natural deformation under crustal pressure conditions.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Without differential stress, hydrostatic stress may be enough to close cracks, and hence, they are not observable from elastic properties. However, while a strong recovery is observed on wave velocity during subsequent unloading, damage produced during loading remains within the rock specimens and are expected to affect other physical properties, such as permeability or porosity (Sarout et al, ). Our results suggest that elastic measurement of natural rock samples should be made with both confining pressure and deviatoric stress to highlight the full amount of damage recorded from natural deformation under crustal pressure conditions.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…In practice, the permeability for a medium made exclusively of tube‐like pores is κ tube ~10 −13 m 2 (e.g., Sarout, ). For purely cracked media, one, however, expects a value of κ c ~10 −17 to 10 −18 m 2 at the lowest pressure (e.g., Benson, Schubnel, et al, ; Sarout et al, ). Hence, if κ t ( P c ) is additive (equation ), the contribution of the cracks to the total flow is negligible compared to that of the subnetwork of tubes and κ t ( P c ) ~ κ tube .…”
Section: Discussion: Pressure Dependence Of Transport Propertiesmentioning
confidence: 99%
“…Elastic properties of the samples were determined from the measured density ρ and the ultrasonic velocities measured along the x 1 , x 2 , and x 3 directions using the noninteracting crack effective medium approach (Kachanov, 1994). While numerous effective elastic medium theory models of cracked materials have been developed over the last 30 years (e.g., Eshelby et al, 1951;Hudson, 1981;O'Connell & Budiansky, 1974;Walsh, 1965), the range of validity of one of the simplest effective elastic medium theories, Kachanov's (1994) noninteractive crack model, has been shown to extend to relatively high crack densities, including for symmetries up to orthorhombic (Sarout et al, 2017;Schubnel et al, 2006). For example, Snyder et al (2015) showed good agreement between the predictions of Kachanov's crack model and direct measurements of crack densities in columnar ice for single set crack densities (i.e., α ii , see below) up to~0.1.…”
Section: Appendix Amentioning
confidence: 99%